The water-gas shift reaction on pt/γ-ai2O3 catalyst: operando ssitka-drifts-mass spectroscopy studies - Efstathiou, Angelos M.; Kalamaras, Christos M.; Olympiou, Georgios (My University, 2008)
Steady-state isotopic transient kinetic analysis (SSITKA) experiments coupled with in situ DRIFTS and mass spectrometry (operando) were performed for the first time to study essential mechanistic aspects of the water-gas shift reaction (WGSR) over a 0.5 wt.% Pt/γ-Al2O3 catalyst. The chemical structure of active and inactive reaction intermediate species present in the carbon-path ("C-path") from CO to the CO2 product gas (use of 13CO) and in the hydrogen-path ("H-path") from H2O to the H2 product gas (use of D2O) of the reaction mechanism were determined. In addition, the concentrations (μmol/g) of active species in both the "C-path" and "H-path" of the WGSR at 350 °C were measured. Based on the large concentration of active species present in the "H-path" (OH/H located on the alumina support), the latter being larger than 28 equivalent monolayers of the exposed Pt metal surface, the small concentration of OH groups along the periphery of metal-support interface, and the significantly smaller concentration (μmol/g) of active species present in the "C-path" (adsorbed CO on Pt and COOH species on the alumina support and/or the metal-support interface), it might be suggested that diffusion of OH/H species on the alumina support surface towards Pt catalytic sites present in the "H-path" of reaction (back-spillover process) might be considered as a slow reaction step. The latter process was evidenced after conducting the WGS reaction (CO/H2O) in a partially deuterated alumina surface (Pt/γ-Al2O3). At least two kinds of formate (-COOH) species residing on the alumina surface have been identified, one of which was active and leads to the formation of CO2(g) and H2(g), whereas the other kind(s) is/are considered as inactive (spectator) adsorbed reaction intermediate species.
Keywords: Water-gas; Mass spectrometry; Water--Analysis